Estudo dos impactos resultantes do uso e ocupação do solo da agrovila da barragem Rosário, no Ceará, e do seu entorno, e suas implicações no reservatório - Lima, Paulo de Tarso Feitosa (2013)
The management of water resources requires an analysis of biotic, abiotic and anthropogenic means, part of the basic management unit which is the catchment area, which is why it is necessary to your monitoring. This study aimed to verify the actual use and occupation of the dam agrovila Rosary / EC and its surroundings, and its impact on the prevention management of the quantity and quality of water from the reservoir, to situate themselves in the area adjacent to reservoir is to have a vision, economic, social and environmental sustainability of the current level of development, wellness and sustainability inserted therein population. The study includes survey with state and local for obtaining documents and data on the current legislation , studies in the area and other relevant information to Rosario dam , Ceará , and his agrovila public agencies, Questionnaire over 13 families residing in their surroundings, all within a radius of 2.0 Km Ao was applied to all households in the agricultural community , a total of 26 , and 39 families were interviewed for knowledge of current social, economic , environmental and institutional . The paper also presents quantitative and qualitative data reservoir water Rosario.